2018
DOI: 10.1212/wnl.0000000000006497
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences in burnout, career satisfaction, and well-being in US neurologists

Abstract: ObjectiveTo examine age and sex differences in burnout, career satisfaction, and well-being in US neurologists.MethodsQuantitative and qualitative analyses of men's (n = 1,091) and women's (n = 580) responses to a 2016 survey of US neurologists.ResultsEmotional exhaustion in neurologists initially increased with age, then started to decrease as neurologists got older. Depersonalization decreased as neurologists got older. Fatigue and overall quality of life in neurologists initially worsened with age, then sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 43 publications
4
58
1
4
Order By: Relevance
“…A recent study of burnout revealed that, in response to the open ended question, "Is there anything else you would like to share with AAN (American Academy of Neurology) regarding burnout and wellbeing?" women neurologists more commonly wrote about depression and suicidal ideation than did men neurologists [22].…”
Section: Burnout Depression and Suicidementioning
confidence: 97%
See 1 more Smart Citation
“…A recent study of burnout revealed that, in response to the open ended question, "Is there anything else you would like to share with AAN (American Academy of Neurology) regarding burnout and wellbeing?" women neurologists more commonly wrote about depression and suicidal ideation than did men neurologists [22].…”
Section: Burnout Depression and Suicidementioning
confidence: 97%
“…Women expressed more concerns than men about declining professionalism in medicine. Women, but not men, commented about the loss of the academic mission in the current health care environment [22].…”
Section: Prevalencementioning
confidence: 99%
“…The recent Medscape National Physician Burnout, Depression and Suicide Report (2019) on over 15,000 doctors showed that burnout was self-reported by 50% of women and 38% of men physicians. In the scientific literature, studies reporting either no significant differences between the sexes [60,61] as well as indications that female doctors are more sensitive to burnout [62][63][64] are also available. Among the studies included in this review results also varied.…”
Section: Gender and Bs In Physiciansmentioning
confidence: 99%
“…For public health workers, we need to consider difference of population characteristics and occupational environment at three tiers to analyse whether these factors will affect their job burnout. In terms of individual factors, previous studies confirmed that gender, age, educational background and years of employment can influence the burnout levels (Cañadas‐De La Fuente et al, ; LaFaver et al, ; WangLv, Qian, & Zhang, ). The importance of these factors to public health workers' burnout is different.…”
Section: Introductionmentioning
confidence: 80%